Over-expression of nuclear factor-κB family genes and inflammatory molecules is related to chronic obstructive pulmonary disease - Zhou, Liting; Liu, Ying; Chen, Xin; Wang, Shuyue; Liu, Hongbo; Zhang, Tianrong; Zhang, Yuezhu; Xu, Qi; Han, Xu; Zhao, Yaming; Song, Xinyue; Ye, Lin (International journal of chronic obstructive pulmonary disease, 2018)
Nuclear factor-κB (NF-κB) signaling plays essential roles in inflammatory responses. However, whether the expression levels of NF-κB family genes affect inflammatory responses is unclear. Moreover, little is known regarding the association between NF-κB family genes expression and the pathogenesis of chronic obstructive pulmonary disease (COPD). The present study was undertaken to assess the relationship between the expression levels of NF-κB family genes mRNA and of inflammatory markers relevant to COPD pathogenesis. A total of 186 unrelated patients with acute exacerbations of COPD and 180 healthy controls were recruited. Total RNA was extracted from the peripheral fasting blood of each subject using trizol reagent. The mRNA levels of NF-κB family genes ( , and ) were measured by real-time quantitative polymerase chain reaction. The serum levels of cyclooxygenase-2 (COX-2), C-reactive protein, interleukin (IL)-1β, IL-6, IL-8, IL-12 and tumor necrosis factor-α were measured with enzyme-linked immunosorbent assay kits. The relative mRNA levels of the NF-κB family genes and the levels of inflammatory molecules were significantly higher in the COPD group than in the control group after adjustment for smoking. The IL-1β, IL-8 and COX-2 levels were significantly lower in the under-expression subgroup as compared to the over-expression subgroup. The COX-2 level was significantly lower ( < 0.05) in the under-expression subgroup as compared to the over-expression subgroup. over-expression was associated with IL-1β, IL-8 and COX-2 levels, whereas overexpression was associated with COX-2 level. Over-expression of both and was found to be related to COPD.